2021
DOI: 10.1038/s41598-021-98343-8
|View full text |Cite
|
Sign up to set email alerts
|

Low serum vitamin D concentrations in Spring-born dairy calves are associated with elevated peripheral leukocytes

Abstract: A role for vitamin D in the immune system is emerging from human research but data in the bovine is limited. In the current study, 48 Holstein–Friesian calves were randomly assigned to one of 4 groups designed to expose calves to divergent vitamin D levels for a 7 month period and to determine its effects on circulating immunity in young calves. Concentrations of circulating 25-hydroxyvitamin D (25OHD) was measured in serum using a commercial ELISA with validated bovine standards. Results showed that mean circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…In this study, all cows are emerging from a period of housing during the winter months, and therefore reduced exposure to sunlight is likely to be a critical contributor to the low 25(OH)D concentrations detected. This is supported by our recent findings in spring-born Holstein-Friesian dairy calves (Flores-Villalva et al 2021 ).…”
Section: Resultssupporting
confidence: 90%
“…In this study, all cows are emerging from a period of housing during the winter months, and therefore reduced exposure to sunlight is likely to be a critical contributor to the low 25(OH)D concentrations detected. This is supported by our recent findings in spring-born Holstein-Friesian dairy calves (Flores-Villalva et al 2021 ).…”
Section: Resultssupporting
confidence: 90%
“…The absolute values of correlation coefficients of IL-8 and neutrophil percentage were >0.7, which indicated that 25(OH)D was strongly correlated with IL-8 and neutrophil percentage, and weakly correlated with other factors. Flores-Villalva et al (25) found that the number of neutrophils in the experimental group (Spring born calves supplemented with commercial calcium containing pellets) was statistically significant decreased compared with the control group, which was consistent with our results. Some scholars have also shown that vitamin D3 supplementation in healthy people can reduce the serum level of IL-8, and its production was controlled by vitamin D through up-regulating the transcription of the anti-inflammatory gene DUSP1 (double specific phosphatase 1) (26,27).…”
Section: Discussionsupporting
confidence: 93%
“…Although there are limited studies in calves, a study conducted in calves with enzootic pneumonia reported that vitamin D concentrations were decreased in diseased animals 4 . What we do know is that vitamin D concentrations are lower in calves from birth until they are 3 months old that serum vitamin D concentrations may not increase despite vitamin supplementation during this early age, and that there is a lack in the development of immunity, making these young animals prone to lung diseases 13 . Accordingly, it has been suggested that serum vitamin D concentrations should be measured in young calves.…”
Section: Discussionmentioning
confidence: 99%
“…The study animals consisted of a total of 30 Holstein calves, aged 3–5 months, under the same management and feeding conditions. The number of animals used in the study was determined based on previous studies 13,14 . All calves were group‐housed in individual hutches outdoors during the study period and had ad libitum access to calf starter (Emek Feed Company, Turkey) and water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation